YANG MENANGIS DI BALIK PELAMINAN KARYA ALDA MUHSI: PANDANGAN DAN NILAI PERNIKAHAN ADAT DALAM CERPEN - Marsten Lihardo Tarigan; Ambarwati, Estiani (Fakultas Bahasa dan Sastra Universitas PGRI Kanjuruhan Malang, 2024)
Marriage is a part of the human life cycle that plays an important role in various aspects of human life.Marriage can be seen as something important because it contains values. Marriage can be seen as a social institution, so marriage regulates relationships between individuals in determining their respective roles and responsibilities. In many Indonesian literary works, you can find images ofmarriage. This research uses the short story Yang Menangis di Balik Pelaminan by Alda Muhsi toexamine the views of the characters and the value of traditional marriage contained in the short story. The short story is analyzed using literary sociology to see the phenomenon of traditional marriage and its value. This research found that there were differences in the views of figures regarding traditional marriage. There are views of figures who state the importance of traditional marriages and there are also views which believe that traditional marriages no longer need to be implemented. This is because times have changed. The result of the next discussion is regarding the value of traditional marriage inshort stories. There are three values in traditional marriage, namely, value in terms of human needs,value in terms of human ability to capture and develop it, value seen from cultural processes.